Understanding the Wellbeing Effects of a Community Music Program for People With Disabilities: A Mixed Methods, Person-Centered Study - MacGlone, Una M.; Vamvakaris, Joy; Wilson, Graeme B.; MacDonald, Raymond A. R. (Frontiers in Psychology, 2020)
People with disabilities face inequalities in mental wellbeing, for which social exclusion is a contributing factor. Musical activities offer a promising but complex intervention, making impacts on a population with highly varied characteristics and needs challenging to capture. This paper reports on a mixed methods, person-centred study investigating a community music intervention for such a population. Three groups of adult service users with varied disabilities (either physical, learning or both), took part in weekly music workshops in different locations. Music staff, housing and resource centre staff, as well as participants and members of their families, took part in semi-structured interviews. A quantitative measure administered by service staff was used to rate service users’ social development. Two lay researchers, both individuals with a disability contributed to all aspects of the study. Interviews were analysed through thematic analysis. Improvements in individuals’ self-expression, confidence, mood and social skills were consistent with previous findings. Differences in effect between centres included: Group 1, some of whom had previous experience of workshops, showed an improvement in musical skills; Group 2 showed a mixed response, some participated with enthusiasm but others chose art activities over music workshops; Group 3 had lasting positive impact, this group had very limited opportunities for music due to their rural location. Quantitative analysis showed significant increase over all groups in communication, interaction with others and joint attention. The intervention was beneficial for participants in separate locations in similar ways, but also highlighted that context and prior experience mediated effects in distinct ways. The lay researchers enhanced the qualitative analysis by emphasising 1. the importance of recognising participants’ self-expression in non-verbal modes of communication, and, 2. the importance of having music staff with a disability to provide a positive role model. This paper proposes that mixed methods person-centred research is the most suitable approach to capture and understand the multiple and varied effects of this complex intervention for a diverse group of participants.